KAJIAN ANTROPOLOGIS TERHADAP RITUAL MEBULLE BAI SEBAGAI MODEL PENYELESAIAN KONFLIK DALAM MASYARAKATDI DESA BUNTUBUDA KECAMATAN MAMASA - Yanti Taruk Tangko (Adisam Publisher, 2025)
The Mebulle Bai ritual in Buntubuda Village, Mamasa District, is a local cultural heritage that serves as a model for conflict resolution within the community. This study employs an anthropological approach based on Stephen B. Bevans’ contextual theology model, which emphasizes valuing local culture as a medium for living out biblical values. Mebulle Bai reflects the principles of reconciliation, forgiveness, and relationship restoration through acknowledgment of mistakes, apologies, and collective community involvement. This aligns with biblical teachings, such as 2 Corinthians 5:18- 19 and Matthew 6:14-15, which emphasize the ministry of reconciliation and the importance of forgiveness in fostering harmonious relationships. This ritual conveys values of respect for ancestors, collective responsibility, and restorative justice that prioritize relationship healing over punishment. Mebulle Bai also serves as an example of contextual theology that integrates faith and culture, bringing God’s love into daily practices. Thus, this ritual not only functions as a means of conflict resolution but also shapes community identity in alignment with Gospel values, fostering sustainable social and spiritual harmony.